FAKTOR YANG MEMPENGARUHI WISATAWAN BERKUNJUNG DI DAYA TARIK WISATA AIR PANAS SEMURUP DITINJAU DARI PUSH FACTOR DAN PULL FACTOR - Sherina Tri Alkhisa; Dwi Pratiwi Wulandari (Ensiklopedia of Journal, 2023)
This research is motivated by the existence of Push Factor and Pull Factor. The aim of this research is to determine the extent to which factors influence tourists visiting the Semurup Hot Springs tourist attraction. The research methodology used in this research is descriptive using quantitative data. This research focuses on tourists who visit the Semurup Hot Springs tourist attraction related to Push Factor and Pull Factor. The large number of samples in the research consisted of 190 respondents, and the sampling technique was non-probability sampling. The analysis technique used in data collection is by distributing questionnaires using a likert scale which has gone through a rigorous assessment to determine its validity and reliability. The findings of this research show that the Push Factor indicator shows a score of 43.20% in the unfavorable category, while the Pull Factor indicator shows a score of 44.43% in the unfavorable category. This means that the influence of Push Factor and Pull Factor on the tourist decision making process in visiting the Semurup Hot Springs tourist attraction is less influential.Keywords: Push Factor, Pull Factor